2008
DOI: 10.1590/s0101-31222008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Nodulação e desenvolvimento de plantas oriundas de sementes de soja teores de molibdênio

Abstract: O fornecimento de molibdênio às plantas é feito, na maioria das vezes, por meio do tratamento de sementes. Contudo, a utilização de sementes enriquecidas com Mo é uma alternativa viável. Nesse trabalho, foram avaliados a nodulação e o desenvolvimento das plantas de soja oriundas de sementes de plantas que receberam aplicação foliar de diferentes doses de Mo. O Mo foi fornecido por meio de aplicações foliares durante o processo de maturação, em aplicação única e parcelada em duas vezes, entre os estádios R5.2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
3
3
0
3
Order By: Relevance
“…The results are in accordance with the results found by Milani et al (2008), who observed that the content of molybdenum within the seed positively influenced the height in plants.…”
Section: Resultssupporting
confidence: 93%
“…The results are in accordance with the results found by Milani et al (2008), who observed that the content of molybdenum within the seed positively influenced the height in plants.…”
Section: Resultssupporting
confidence: 93%
“…This fact happened, possibly, due to the 30 DAE, the plant was in the period of flowering. The flowering period corresponds to the period of maximum nodulation, in other words, occurs at 30 DAE an establishment of the number of nodules, mainly in the main root, reflecting directly in its fresh and dry mass [22]. According to the results shown in Table 7, it can be verified that the residual dose of 80 kg·ha −1 of P 2 O 5 promoted higher number of pods per plant (NPP), but did not differ from the other doses, except for the control treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Esta variable ha mostrado respuestas diferentes a la aplicación de Co y Mo en varias investigaciones. Por ejemplo, Milani et al (2008) en un estudio de fertilización foliar con Mo en soja, observaron que la altura de plantas varió significativamente entre los diferentes tratamientos aplicados. En contraste, Meschede et al (2004) no encontraron diferencias significativas para esta variable cuando aplicaron Mo y Co vía tratamiento de semillas y fertilización foliar.…”
Section: Resultados Y Discusiónunclassified